Effect of eliminating open defecation on diarrhoeal morbidity: an ecological study of Nyando and Nambale sub-counties, Kenya - John Njuguna (BMC Public Health, 2016)
Abstract Background Defecating in the open predisposes people to soil transmitted helminthes and diarrhoeal diseases. An estimated 5.6 million Kenyans defecate in the open. Kenya launched a program to eradicate open defecation by 2013 in the rural areas. By end of 2013, only two sub-counties had eliminated open defecation. These are Nambale and Nyando. The study looked at the impact of eradicating open defecation on diarrhea prevalence among children in these two sub-counties. Methods Data on diarrhoea morbidity among children under 5 years was extracted from the Kenya Health Information System for all the sub-counties in Busia and Kisumu counties for 2012, 2013 and 2014 respectively. Prevalence was calculated for each sub-county in Kisumu for comparison with Nyando’s. Prevalence was also calculated for each sub-county in Busia County and compared to that of Nambale sub-county. A Mann–Whitney U Test was done to test the null hypothesis that diarrhoea prevalence was similar in both open defecation and open defecation free sub-counties. Results A Mann–Whitney U Test revealed significant difference in diarrhoeal prevalence of open defecation sub-counties (Md = 18.4, n = 34) and open defecation free sub-counties (Md = 9.8, n = 5), U = 9, z = −3.2, p = .001. Among the two Counties, Nambale had the lowest prevalence. It recorded a decline from 9.8 to 5.7 % across the three years. Prevalence for diarrhoea cases in Nyando declined from 19.1 to 15.2 % across the three years. Nyando initially had the second highest prevalence in Kisumu County and by 2014 it had the lowest prevalence. Conclusions The two sub-counties with open defecation free status had lower prevalence of diarrhoea cases compared to sub-counties which were yet to attain open defecation free status. This suggests that elimination of open defecation may reduce the number of diarrhoea cases.